Cull Cow Beef Quality Issues: Bruising, Condemnation, and Foreign Objects - Amie Imler; Matt Hersom; Todd Thrift; Joel Yelich; Max Irsik (EDIS, 2014)
Cull cattle are those that are sold from a herd for lack of performance, lack of resources, or genetic improvement. The non-fed beef cattle market (cattle that are not managed through traditional feedlot finishing systems) is comprised primarily of cull cows and bulls. This 4-page article is one of the Cull Cow Beef Quality Issues series, which addresses liability and food safety concerns. It also discusses some quality defects identified in the non-fed beef market, how to prevent them, and how to address them when they appear in cattle. Written by Amie Imler, Matt Hersom, Todd Thrift, Joel Yelich, and Max Irsik, and published by the UF Department of Animal Sciences, December 2014.